A narrative review on the role of cytokines in the pathogenesis and treatment of familial Mediterranean fever: an emphasis on pediatric cases - Chaaban, Ahlam; Yassine, Hasan; Hammoud, Razane; Kanaan, Ruba; Karam, Louna; Ibrahim, José-Noel (Frontiers in Pediatrics, 2024)
Familial Mediterranean Fever (FMF) is a hereditary autoinflammatory disease characterized by an early onset of recurrent fever and serositis episodes. FMF is caused by mutations in the MEFV gene which encodes the pyrin protein, an IL-1β mediated inflammation regulator. Recent findings have identified a plethora of molecules and pathways involved in the regulation of inflammation and innate immunity, hence increasing our understanding of the etiology and inflammatory nature of FMF. Cytokines, in particular, have been found to play a key role in the pathogenesis and treatment of the disease. Indeed, various studies associated cytokines’ genetic variations and expression with susceptibility to and severity of the disease, which was further supported by the positive response of patients, both children and adults, to targeted cytokine blocking therapies. These studies highlighted the potential use of cytokines as biomarkers and target in resistant/intolerant patients and contributed to improving the early detection of FMF in children, thus enhancing their quality of life and providing alternative treatment for severe cases. The aim of this review is to provide the latest updates on the pivotal role of cytokines in FMF and to discuss the efficacy and safety of anti-cytokine biologics by primarily focusing on pediatric FMF cases.